FACTORS INFLUENCING HONEY MARKETING IN CASE OF GIMBO WOREDA; KAFA ZONE - Haile, Melaku Melese (International Journal of Marketing Research Innovation, 2021)
This study was aimed to analyze factors influencing honey marketing efficiency in case of Gimbo woreda; kafa zone with the specific objectives of examining the factors influencing honey marketing efficiency and assessing the level of marketing channels efficiency.  In order to attain these objectives the researcher used primary and secondary data by using structured questionnaire to collect data from a sample of 120 and marketing middleman’s from six rural honey producing kebeles by using judgmental sampling techniques. The analysis of marketing efficiency was made by using marketing margin analysis. The assessment of marketing channels of honey show that there are four marketing participants; these include honey producers, retailers, wholesalers and consumers. Three marketing channels were identified in the study area. First channel involved selling of honey directly from producers to consumers; second channel involved selling honey from producers to retailers to consumers and third channel is Producer – Retailer – Wholesaler – consumers. The results from gross Margin analysis result reveal that beekeepers earned on average birr 1304.892 per hive as a Gross income from the sales of 15.781kg of honey on average. Based on the findings this research recommended policy remedies in order to improve honey marketing efficiency by facilitating reliable market outlet for the beekeeper, establishing marketing organizations (cooperatives) to allow farmers to sell their products at competitive product price. The findings suggests that, effective market service has to be established to provide accurate and timely market information to farmers and traders on current honey demand and prices at national and regional levels. Emphasis should be given to improve producers and marketing middleman’s capacity, through offering credit and other services to improve in the marketing of honey.